Glial Cell Line-Derived Neurotrophic Factor Family Ligands, Players at the Interface of Neuroinflammation and Neuroprotection: Focus Onto the Glia - Kotliarova, Anastasiia; Sidorova, Yulia A. (Frontiers in Cellular Neuroscience, 2021)
Well-known effects of neurotrophic factors are related to supporting the survival and functioning of various neuronal populations in the body. However, these proteins seem to also play less well-documented roles in glial cells, thus, influencing neuroinflammation. This article summarizes available data on the effects of glial cell line derived neurotrophic factor (GDNF) family ligands (GFLs), proteins providing trophic support to dopaminergic, sensory, motor and many other neuronal populations, in non-neuronal cells contributing to the development and maintenance of neuropathic pain. The paper also contains our own limited data describing the effects of small molecules targeting GFL receptors on the expression of the satellite glial marker IBA1 in dorsal root ganglia of rats with surgery- and diabetes-induced neuropathy. In our experiments activation of GFLs receptors with either GFLs or small molecule agonists downregulated the expression of IBA1 in this tissue of experimental animals. While it can be a secondary effect due to a supportive role of GFLs in neuronal cells, growing body of evidence indicates that GFL receptors are expressed in glial and peripheral immune system cells. Thus, targeting GFL receptors with either proteins or small molecules may directly suppress the activation of glial and immune system cells and, therefore, reduce neuroinflammation. As neuroinflammation is considered to be an important contributor to the process of neurodegeneration these data further support research efforts to modulate the activity of GFL receptors in order to develop disease-modifying treatments for neurodegenerative disorders and neuropathic pain that target both neuronal and glial cells.